The Role of Gut–brain Axis in Regulating Glucose Metabolism After Acute Pancreatitis. Issue 1 (January 2017) - Pendharkar, Sayali A; Asrani, Varsha M; Murphy, Rinki; Cutfield, Richard; Windsor, John A; Petrov, Maxim S
Abstract : OBJECTIVES: : Diabetes has become an epidemic in developed and developing countries alike, with an increased demand for new efficacious treatments. A large body of pre‐clinical evidence suggests that the gut–brain axis may be exploited as a potential therapeutic target for defective glucose homeostasis. This clinical study aimed to investigate a comprehensive panel of glucoregulatory peptides, released by both the gut and brain, in individuals after acute pancreatitis. METHODS: : Fasting levels of glucagon‐like peptide‐1 (GLP‐1), glicentin, oxyntomodulin, peptide YY, ghrelin, cholecystokinin, vasoactive intestinal peptide (VIP), and secretin were studied. Modified Poisson and multivariable linear regression analyses were conducted. Pre‐determined concentration ranges were used to categorize each peptide into quartiles. RESULTS: : A total of 83 individuals were included, of who 30 (36%) developed abnormal glucose metabolism (AGM) after acute pancreatitis. In individuals with AGM, the highest quartile of oxyntomodulin differed most significantly from the lowest quartile with a prevalence ratio (PR; 95% confidence interval) of 0.50 (0.21, 1.20; P =0.005); of glicentin with a PR of 0.26 (0.13, 0.54; P <0.001); and of VIP with a PR of 0.34 (0.13, 0.89; P =0.043). Peptide YY, GLP‐1, cholecystokinin, ghrelin, and secretin were not significantly associated with AGM. CONCLUSIONS: : Fasting circulating oxyntomodulin, glicentin, and VIP levels are significantly decreased in patients with defective glucose homeostasis after acute pancreatitis. Oxyntomodulin appears to be a promising therapeutic target for future clinical studies on diabetes associated with diseases of the exocrine pancreas.